2001
DOI: 10.1016/s0022-5347(05)65925-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sex Hormones on Renal Osteopontin Expression and Urinary Constituents in Experimental Urolithiasis

Abstract: Testosterone appears to promote stone formation by suppressing osteopontin expression in the kidneys and increasing urinary oxalate excretion. Estrogen appears to inhibit stone formation by increasing osteopontin expression in the kidneys and decreasing urinary oxalate excretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 16 publications
6
37
1
2
Order By: Relevance
“…Studies have reported the potential inhibitory role of female hormones in urinary stone formation. Male gender has been associated with greater number of stone episodes (16,(18)(19). Memon (22) in Saudi observed that the male to female ratio was 500:100, which is almost comparable to the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have reported the potential inhibitory role of female hormones in urinary stone formation. Male gender has been associated with greater number of stone episodes (16,(18)(19). Memon (22) in Saudi observed that the male to female ratio was 500:100, which is almost comparable to the present study.…”
Section: Discussionsupporting
confidence: 88%
“…vitamin C, xylitol (sweetener), or hydroxyproline (20)), mechanisms of oxalate transport in the kidney or intestine, and/or endogenous oxalate production. Studies in rats suggest that testosterone increases and estrogen decreases urinary oxalate excretion(21). A recent study in mice that lack the hepatic androgen receptor (AR) documented reduced oxalate biosynthesis (22), and that mice lacking kidney proximal or distal epithelial AR also had lower CaOx crystal formation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, testosterone may increase the risk of NL. Indeed, many studies have demonstrated that testosterone was associated with the presence of NL [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hormonal factors play a role in the development of nephrolithiasis (NL). For instance, insulin resistance [2, 3] and testosterone [46] were found to be related with increased NL. Ando et al showed that insulin resistance was higher in stone formers of Japanese descent [7].…”
Section: Introductionmentioning
confidence: 99%